The Paradoxes of Open Educational Resources. - Cope, Bill; Kalantzis, Mary (Information, Medium & Society: Journal of Publishing Studies, 2023)
The era of digital media has spawned a number of "open" movements. These represent new domains of "social production" resistant to commercialism: open-source software, open access scholarly publishing, and Open Educational Resources (OERs). This article focuses on OERs, while also ranging more widely to explore paradoxes in the idea and practice of "open." On the one hand, "open" movements make intellectual property freely accessible and reusable for all. On the other hand, this openness favors Big Tech companies that base their search and artificial intelligence businesses on open content. When content is not open, they treat it as if it were, copying copyrighted material without permission. The article explores the consequences of these developments for the economics of educational content development, contrasting such practices with traditional publishing models. With its high textbook prices and journal subscription fees, traditional publishing is far from blameless. However, in the "open" regime, the creative work of authors, publishers, and educational content creators is being pushed into the realm of unpaid labor. We conclude by suggesting some solutions.